Two Dimensional Crack Problem - Srivastava, K. N.; Kumar, M. (Defence Science Journal, 2014)
An alternative method of finding distribution of stress in a long isotropic elastic cylinder containing a strip crack situated symmetrically on a diametral plane is presented here. The problem is reduced to the solution of a Fredholm integral equation of second kind by making use of suitable integral representation of complex potentials.